정상 한국인에서 연령에 따른 망막 혈관 직경과 관련 인자에 대한 분석 - 임종찬; Jong Chan Im; 신재필; Jae Pil Shin; 김인택; In Taek Kim; 박동호; Dong Ho Park (Daihan angwa haghoi jabji, 2014)
목적: 정상 한국인을 대상으로 망막 동정맥의 직경을 측정하고, 연령에 따른 망막 혈관 직경의 변화와 망막 혈관 직경에 영향을 미치는 인자에 대하여 알아보고자 한다. 대상과 방법: 정상인 152명의 안저 사진을 촬영하고, 컴퓨터 프로그램(IVAN)을 이용하여 central retinal artery equivalent (CRAE)와 centralretinal vein equivalent (CRVE)를 측정하고, 연령, 성별, 고혈압, 당뇨, 흡연과 같은 관련 인자와 망막 혈관 직경과의 관계를 분석하였다. 결과: 정상 한국인의 망막 혈관 직경은 CRVE 209.33 ± 12.40 μm, CRAE 149.70 ± 9.01 μm로 측정되었고 연령이 증가함에 따라CRVE와 CRAE는 감소하였다(p＜0.001, respectively). CRVE와 CRAE는 남자가 여자보다 유의하게 크게 측정되었다(p=0.002,p=0.042, respectively). 연령과 성별을 통제한 후, 고혈압군의 CRVE와 CRAE는 비고혈압군에 비해 유의하게 작았으며(p=0.038,p=0.032, respectively), 흡연자군과 비흡연자군, 당뇨군과 비당뇨군에 대한 CRVE와 CRAE의 차이는 유의하지 않았다(p＞0.05, respectively). 결론: 정상 한국인의 망막 혈관 직경은 연령이 증가함에 따라 작아졌다. 성별과 고혈압은 망막 혈관 직경에 영향을 미치는 인자이며, 흡연과 당뇨는 영향을 미치지 않았다. Purpose: To measure the diameter of the retinal arterial and venous caliber of normal Korean subjects and evaluate the factors affecting these diameters. Methods: Fundus photography was performed on 152 normal Korean subjects. Central retinal artery equivalent (CRAE) and central retinal vein equivalent (CRVE) were measured with a computer-based program (IVAN), and were used to investigate the relationship between the diameter and factors including age, gender, hypertension, diabetes, and smoking. Results: Among the study subjects, the CRVE was 209.33 ± 12.40 μm and the CRAE was 149.70 ± 9.01 μm. The CRVE and CRAE decreased with increasing age in all study subjects (both p < 0.001). There were significant gender differences in the CRVE and CRAE (p = 0.002, p = 0.042, respectively). After adjusting for age and gender, the hypertension group showed smaller CRVE and CRAE than the non-hypertension group (p = 0.038, p = 0.032, respectively). Smoking and diabetes were not significant factors affecting the CRAE and CRVE (both p > 0.05). Conclusions: In our study group, retinal vascular caliber of normal Korean subjects decreased with aging. Retinal vascular caliber was affected by gender and hypertension, but not by smoking and diabetes.